PEDAGOGICAL AND PSYCHOLOGICAL BASES ON DEVELOPING STUDENTS’ PROFESSIONAL THINKING IN MEDICAL PEDAGOGICAL EDUCATION - N, Kurbanova G. (International Journal of Psychosocial Rehabilitation, 2020)
The article explores the development of professional thinking of future professionals on the basis of pedagogical and psychological principles, emphasizes the importance of culture of thinking and pedagogical communication in this process, theoretical foundations, methodological principles and results of empirical research. The research revealed the pedagogical and psychological peculiarities of the professional thinking of students in the field of medical pedagogy. And our developing authorship program has been an important impetus for the development of the professional thinking of future professionals.